Evaluating the Potential of Sea Surface Height Observations and Depth Datum Calculation Using GNSS/IMU Buoys - Chung-Yen Kuo; Wen-Hau Lan; Chi-Ming Lee; Huan-Chin Kao (Journal of Marine Science and Engineering)
This study evaluates the potential of GNSS/IMU buoys for sea surface height observations and depth datum verification. GNSS/IMU buoys were deployed alongside 34 tide gauges around Taiwan for synchronous sea surface height measurements. The collected GNSS data were processed through relative positioning and loosely coupled GNSS/IMU integration methods. Analysis revealed that the average of the means of the differences was −2.5 cm across all stations, indicating that most tide gauge datums agreed well with the GNSS/IMU buoy measurements. Significant discrepancies were observed at only a few stations, likely due to local subsidence. Notably, the Shuitou station showed a mean difference of 63.4 cm, resulting from its remarkable deviation from tidal zero since 2019, suggesting a potential datum issue. The mean of the standard deviation (STD) of the differences across the stations was 3.8 cm, with the highest STD observed at the Shuitou station (9.4 cm). These findings demonstrate that GNSS/IMU buoys can effectively complement tide gauge measurements for observing sea surface heights and defining the depth datum, particularly in areas where local vertical land movements affect tide gauge data accuracy.